2015
DOI: 10.1021/acs.est.5b01952
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Partial Denitrification and Mixotrophic Growth of NOB on Microbial Distribution in Aerobic Granular Sludge

Abstract: In aerobic granular sludge (AGS), the growth of nitrite oxidizing bacteria (NOB) can be uncoupled from the nitrite supply of ammonia oxidizing bacteria (AOB). Besides, unlike for conventional activated sludge, Nitrobacter was found to be the dominant NOB and not Nitrospira. To explain these experimental observations, two possible pathways have been put forward in literature. The first one involves the availability of additional nitrite from partial denitrification (nitrite-loop) and the second one consists of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 55 publications
0
15
0
1
Order By: Relevance
“…The predominance of Nitrobacter sp. in the NOB population in aerobic granules may result from the fact that they can both oxidize nitrite produced during partial denitrification (nitrite-loop) and grow mixotrophically in the presence of acetate (ping-pong), reducing the content of carbon in wastewater [39].…”
Section: Molecular Studiesmentioning
confidence: 99%
“…The predominance of Nitrobacter sp. in the NOB population in aerobic granules may result from the fact that they can both oxidize nitrite produced during partial denitrification (nitrite-loop) and grow mixotrophically in the presence of acetate (ping-pong), reducing the content of carbon in wastewater [39].…”
Section: Molecular Studiesmentioning
confidence: 99%
“…Denitrification is achieved under anaerobic or anoxic conditions1314. However, sporadic reports on aerobic denitrifiers have induced aerobic denitrification using nitrate-oxidizing agents under aerobic conditions9.…”
mentioning
confidence: 99%
“…The results showed that Proteobacteria (average relative abundance (RA), 63.4%) was the most abundant phylum across all the samples, followed by Bacteroidetes (average RA, 22.4%), which was also found with a high abundance in other marine MBBRs [45][46][47]. The integration of MA with MBBR significantly [48], and many Bacteroidetes species have been reported to have the capacity for organic carbon degradation [49]. The relatively lower abundance of Nitrospirae in MBBR-MA biofilter samples could be explained by the relatively lower nitrite concentration detected in the MBBR-MA system (Figure 2(b)), because macroalgae also contribute to ammonia and nitrite removal.…”
Section: Beta Diversity Analysismentioning
confidence: 91%